Periodic Due Date Assignment with Family Setups - Sertdemir, Sevilay; Unal, Ali Tamer; Duzgit, Zehra (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
In this study we consider a single machine due date assignment problem involving dynamic job arrivals and family setups. The due date quotation process that we investigate is based on periodically generating schedules of new and existing jobs, and quoting due dates using a function of completion times of jobs in the schedule. We propose a mixed integer linear programming formulation to solve the underlying scheduling problem. We also present a function to quote due dates for new jobs. We report the performance of the proposed due date quotation process based on the simulation study that is carried out under various shop and solution procedure parameters.